2018
DOI: 10.1155/2018/5190816
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Asymmetry of Gait and Muscle Torque in Patients after Unilateral Transfemoral Amputation

Abstract: Many studies have shown that unilateral transfemoral amputation involves asymmetric gait. Transfemoral amputation leads to muscle atrophy in a tight stump resulting in asymmetry in muscle torque between the amputated and intact limb. This research is aimed at verifying if a relationship between torque values of hip joint flexors and extensors and gait asymmetry in patients with TFA exists. Fourteen adult subjects with unilateral TFA took part in the experiment. Gait symmetry was evaluated based on the ground r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…There are many indices in functional diagnostics used to assess the degree of asymmetry; these have been used by many researchers and are as follows: symmetry index [2, 10, 11], relative difference index [12], relative asymmetry index [13], symmetry ratio [14], asymmetry ratio [15], integral index symmetry [16], symmetry angle [17], or the standard deviation of the differential index for upper limbs [18]. One of them, the symmetry index (SI), proved to be the most reliable tool for the assessment of side deviations in human movements and is widely used in movement analysis [19–21]. Unfortunately, the formula proposed originally by Robinson et al [10] has some limitations, namely, SI being a single number, differences being compared against average values, and being ineffective overall for variables of small values.…”
Section: Introductionmentioning
confidence: 99%
“…There are many indices in functional diagnostics used to assess the degree of asymmetry; these have been used by many researchers and are as follows: symmetry index [2, 10, 11], relative difference index [12], relative asymmetry index [13], symmetry ratio [14], asymmetry ratio [15], integral index symmetry [16], symmetry angle [17], or the standard deviation of the differential index for upper limbs [18]. One of them, the symmetry index (SI), proved to be the most reliable tool for the assessment of side deviations in human movements and is widely used in movement analysis [19–21]. Unfortunately, the formula proposed originally by Robinson et al [10] has some limitations, namely, SI being a single number, differences being compared against average values, and being ineffective overall for variables of small values.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum value of the vertical ground reaction force (GRF) component assessed throughout the entire gait cycle was usually the highest in the supporting phase of the TFA gait pattern, and its value for the amputated limb was signi cantly lower than that for the uninvolved limb [29,43,44]. Our previous research showed that variables describing GRF behavior were statistically smaller for the amputated limb regarding values for healthy controls by almost 7.7 percent of body weight (%BW) in the supporting phase, 12.3 %BW in terminal stance, and 12.0 %BW for the posterior braking force at initial stance [25]. Values of the vertical component of GRF during underweight in middle stance were on average 5.8 %BW higher for the amputated limb.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, prolonged time asymmetric loading of the lower limb may result in atrophy of stump muscles and degenerative changes in the joints [25]. The main challenge is to choose the adequate calculation of asymmetry depending on what aspect of gait one wants to assess.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations